2008
DOI: 10.1080/01635580701745327
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Absorption of Auraptene (7-Geranyloxylcoumarin) in Male SD Rats: Comparison With 7-Ethoxycoumarin

Abstract: We previously reported that auraptene (7-geranyloxycoumarin; AUR), a coumarin that occurs widely in citrus fruit, has been shown to be a promising cancer-preventive agent in several rodent models. However, its bioavailability and metabolism have not been investigated. In this study, we compared the metabolism characteristics of AUR with those of 7-ethoxycoumarin (ETC) in male Sprague Dawley rats. Each (500 micromol/kg body weight) was given separately by a single gastric intubation procedure, and digestive tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Tanaka, Yasui, Ishigamori-Suzuki, and Oyama (2008) note that, along with a number of other citrus oil components, it inhibits chronic inflammation and fat build up that predispose laboratory mice to chemically caused colon cancer. Kuki, Hosotani, Ohigashi, and Murakami (2008) note that auraptene stays in circulation longer and seems to have longer lasting effects in stimulating the breakdown of carcinogenic compounds in the kidneys and livers of several types of rodents in which cancers have been experimentally induced, a finding consonant with the results of Tanaka et al (1998), Prince et al (2009), andKleiner et al (2008) who also mention bergamottin in this context. Most recently (Krishnan et al, 2009), auraptene has been cited for its ability to delay breast cancer onset in a number of rodent models by disrupting Cyclin D function, a protein that enables cell division.…”
Section: Citrus Oil Pulp Seed and Juice Components As Anticancer Asupporting
confidence: 68%
“…Tanaka, Yasui, Ishigamori-Suzuki, and Oyama (2008) note that, along with a number of other citrus oil components, it inhibits chronic inflammation and fat build up that predispose laboratory mice to chemically caused colon cancer. Kuki, Hosotani, Ohigashi, and Murakami (2008) note that auraptene stays in circulation longer and seems to have longer lasting effects in stimulating the breakdown of carcinogenic compounds in the kidneys and livers of several types of rodents in which cancers have been experimentally induced, a finding consonant with the results of Tanaka et al (1998), Prince et al (2009), andKleiner et al (2008) who also mention bergamottin in this context. Most recently (Krishnan et al, 2009), auraptene has been cited for its ability to delay breast cancer onset in a number of rodent models by disrupting Cyclin D function, a protein that enables cell division.…”
Section: Citrus Oil Pulp Seed and Juice Components As Anticancer Asupporting
confidence: 68%
“…Coumarins are rapidly absorbed from the gastrointestinal tract and widely distributed [22]. Other coumarins like imperatorin, isoimperatorin and isopimpinellin have also been shown to be orally bioavailable [15,23,24,30]. Auraptene was detected in mammary glands, livers and tumors, suggesting that it is absorbed and distributed to the target organ.…”
Section: Discussionmentioning
confidence: 99%
“…Auraptene was detected in mammary glands, livers and tumors, suggesting that it is absorbed and distributed to the target organ. An article was recently published on the concentrations of auraptene in male Sprague-Dawley rats following oral administration [30]. From 1–4 h following gavage administration (500 μmol/kg bw, p.o.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that detoxification and excretion of carcinogens are the most important function of auraptene for preventing carcinogenesis. Auraptene does not affect carcinogen-activated enzymes such as cytochrome P450s when it is orally administered to mice (Kleiner et al, 2008;Kuki, Hosotani, Ohigashi, & Murakami, 2008). However, auraptene accelerated the activation of metabolic and excretory enzymes such as glutathione S-transferase, suggesting that auraptene may suppress gene mutation by carcinogens in cells (Tanaka et al, 1997(Tanaka et al, , 1998.…”
Section: Introductionmentioning
confidence: 88%